Pharmacological inhibition of CDK7 by THZ1 impairs tumor growth in p53‐mutated HNSCC. (6th February 2021) - Ge, Han; Yao, Yuan; Jiang, Yue; Wu, Xiang; Wang, Yanling
Abstract: Background: Cyclin‐dependent kinase 7 (CDK7) has been critically linked to human cancer. However, the roles of CDK7 in head and neck squamous cell carcinoma (HNSCC) remain incompletely known. Here, we sought to dissect the functions of CDK7 underlying HNSCC tumorigenesis and explore whether pharmacological inhibition of CDK7 could induce anti‐cancer effects. Methods: CDK7 expression was measured in a panel of HNSCC cell lines with p53 mutation and 20 pairs of HNSCC samples and adjacent non‐tumor tissues. Genetic targeting and pharmacological inhibition of CDK7 were conducted to dissect the biological roles of CDK7 in p53‐mutated HNSCC cells. An HNSCC xenograft model was developed to determine the therapeutic effects of THZ1 in vivo. Potential genes and pathways responsible for therapeutic effects of THZ1 were identified by genome‐wide RNA‐sequencing and bioinformatics interrogations. Results: CDK7 expression was significantly elevated in cancerous cells and samples as compared with their adjacent non‐tumor counterparts. Impaired cell proliferation, migration, and invasion as well increased apoptosis were observed in cells upon CDK7 knockdown or THZ1 exposure. THZ1 administration potently inhibited tumor overgrowth in vivo. Mechanistically, hundreds of genes enriched in cell proliferation, apoptosis, and cancer‐related categories were identified to be potentially mediated the therapeutic effects of THZ1 in HNSCC. Conclusion: Our findings reveal that CDK7 might serve as a novel putative pro‐oncogenic gene underlying HNSCC tumorigenesis and therapeutic targeting of CDK7 might be a promising strategy for p53‐mutated HNSCC.